2015
DOI: 10.1016/j.jbusres.2014.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Perceived value and perceived usefulness of halal labeling: The role of religion and culture

Abstract: This research identifies the impact of the perceived value and perceived usefulness of a halal-labeled product, culture and religion on purchase intentions using data from 10 indepth interviews and 303 self-administered questionnaires. Factor analysis and hierarchical multiple regression are used for data analysis. The results show that perceived usefulness, vertical collectivism, horizontal collectivism and religiosity predict a significant amount of variance in intentions. Specifically, perceived usefulness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
226
6
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(261 citation statements)
references
References 47 publications
19
226
6
10
Order By: Relevance
“…In addition, many researchers have proposed that the intention to purchase indicates an individual human belief to buy halal food (Nazahah & Sutina, 2012; Yunus, Rashid, Ariffin, & Rashid, 2014). Therefore, previous studies have shown that the purchase intention is strongly correlated with attitude, halal knowledge and halal quality (Jamal & Sharifuddin, 2015;Khalek, 2014;Khalek & Ismail, 2015;Mohamed Elias, 2016).…”
Section: Halal Food Purchase Intentionmentioning
confidence: 94%
“…In addition, many researchers have proposed that the intention to purchase indicates an individual human belief to buy halal food (Nazahah & Sutina, 2012; Yunus, Rashid, Ariffin, & Rashid, 2014). Therefore, previous studies have shown that the purchase intention is strongly correlated with attitude, halal knowledge and halal quality (Jamal & Sharifuddin, 2015;Khalek, 2014;Khalek & Ismail, 2015;Mohamed Elias, 2016).…”
Section: Halal Food Purchase Intentionmentioning
confidence: 94%
“…In the context of food products, product labels provide a range of benefits for consumers by contributing to the perception related to the value and usefulness of the product. For example, consumers assign high hedonic value to products with an organic label (Sirieix & Tagbata, 2008) because consumers assume that the product has a better taste than non-organic products (McEachern & McClean, 2002), is better for the human body and is more environmentally friendly and morally justifiable (Jamal & Sharifuddin, 2015). In regards to the halal label on the packaging of snacks, the label provides value-expressive benefits for consumers by building a perceived value that is as positive for the consumer as it is for Muslim society.…”
Section: Perceived Value Of Restaurants With Halal Certificationmentioning
confidence: 99%
“…Following Davis (1989), this study defines perceived usefulness as consumers' belief that buying products labeled as halal will enhance their experience in shopping for products (Jamal & Sharifuddin, 2015).…”
Section: Perceived Usefulness Of Halal Certificationmentioning
confidence: 99%
See 2 more Smart Citations